Interhospital Transport of Children With Peripheral Venous Catheters by Private Vehicle: A Mixed Methods Assessment. Issue 1 (8th January 2022) - Mangus, Courtney W.; Canares, Therese; Klein, Bruce L.; Costabile, Philomena; Monroe, David; Noje, Corina; Stevens, Martha W.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Many children seeking emergency care at community hospitals require transport to tertiary centers for definitive management. Interhospital transport via ambulance versus patient's own vehicle (POV) are 2 possible modes of transport; however, presence of a peripheral venous catheter (PIV) can determine transport by ambulance. Caregiver satisfaction, patient comfort, and PIV complications related to POV transport have not been described. Objective: The aims of the study were to examine caregivers' satisfaction and perceptions of POV transport in children with/without PIVs and to assess PIV-related complications during transport. Methods: We performed a mixed-methods, prospective cohort study of children who presented with low-acuity conditions to a community hospital and subsequently required transfer to a pediatric tertiary center. Caregivers of patients with/without PIVs were given the choice of transport by POV or ambulance. Surveys completed after transport used dichotomous, 5-point Likert scale, and open-ended responses to assess satisfaction, perceptions, and PIV-related complications. Responses were quantitatively and qualitatively analyzed accordingly. The receiving hospital assessed PIV integrity. Results: Sixty-nine of 78 eligible patients were enrolled; of those, 67 (97%) elected transport by POV and 55 (82%) completed surveys. Most caregivers had positive responses related to satisfaction, comfort, and safety. Results did not differ significantly between those with/without PIVs. The majority (96%) would choose POV transport again. There were no reported PIV complications; all PIVs were functional upon arrival. Qualitative analysis identified themes of comfort, convenience, and efficiency. Conclusions: In select scenarios, interfacility transport by POV is preferred by families and doing so with a saline-locked PIV does not result in complications.